Foreword - Museology: New Focuses / New Challenges - Moutinho, Mário Canova (Edições Universitárias Lusófonas, 2009)
Certain days, when I wake up in the morning, I have no doubt I am the hunter in the Little Riding Hood’s tale. Free of angst, I am sure of my role in this tale, I know what to do, how to do it, evaluating situations well and defining aims.             In such days, museology as defined by ICOM is easy. The Museum is indeed a permanent institution that collects, keeps, classifies and exhibits objects for cultural, leisure and development purposes; and I do not get traumatised in the search for a definite meaning of the museological object. In such days, in addition, I refuse to acknowledge the new colonisation wars in Iraq, in Cuba, in Candelária or Armenia. I also ignore that 80% of the resources in the planet are for the exclusive use of 20% of humanity, I ignore the dependency on the IMF and the migration of labour towards the North. But, in other days, when I wake up, I am the granny. I have consolidated experiences and foresights, and I know perfectly well that all is provisional. All I have is past. My role in the tale does not force me to question history or its function. I will be reborn as many times as needed, regardless of change.